Effects of prescribed seasonal burning on A combretum-commiphora plant community in South Central Kenya. - Kinyamario, J.I. (Texas A&M University, 1982)
Studies of prescribed seasonal burning on a combretum-commiphora plant community were conducted in Kenya on the National Range Research Station, Kiboko, in 1980-81. Dry and early rainy season burns were applied in different months. Dry season burns were more effective in reducing woody plant canopy cover, height and increasing stem mortality for most species. Early season burns produced greater numbers of resprouts as compared to dry season burns. Numbers of plants for most species showed no significant change due to treatment. Composite plant canopy cover was highly significant (p .001)reduced by January (dry season)burn. Some species, however, had their canopy covers greatly reduced rainy season burns compared to dry season burns, notably, combrtum ariculatum.In some species, comretum apiculatum, Lannea processes and lantana vinbumoides, average plant heights were reduced more following early rainy season burns than after dry season burns. It is my pleasure to thank the rembers of my advisory committee, Dr. Fred E. Smeins, who directed this investigation, Dr. Murray H. Milford and Dr. Stephan L. Hatch. Thanks aslo to the staff of the National Range Research Sation, Kiboko, who provided their time and efforts in this study. Specifically I wish to thank Mr. James Ndemwa Ituli for his time in data colection. Again I want to thank Mr. Trey Richardson for his invaluable help in statistical data analysis and computer work. Finally, thanks to my wife, Kathi, f